PHYTOSOCIOLOGICAL STUDIES OF SELECTED SEMI-ARID SITES IN AL-MAFRAQ JORDAN - S. Damhoureyeh (Journal of Animal and Plant Sciences, 2019)
Two sites, one north facing and another south facing slope, were selected randomly outside Surra Rangeland Reserve in Al-Mafraq governorate of northern Jordan. The two sites belong to Irano-Turanian region and support steppe rangeland vegetation.Thirty six quadrats, each of one square meter were surveyed for each site. Vegetation total cover, dry biomass, and total number of individuals at species and family levels were recorded in each quadrat and averaged per site. Species richness, relative frequency, relative density and importance values were subsequently calculated. Marked difference in species diversity and composition was observed between the two sites. The south-facing site supported lower species richness and fewer plant families. Stipa sp was the most important species in south facing site while Poa bulbosa in north facing. The two sites shared general characteristics of disturbed steppe rangeland, including low productivity and diversity, and both sites dominated by Poaceae and Chenopodiaceae (notably Salsola vermiculata).
Keywords: Herbaceous vegetation cover; Jordan; Steppe vegetation; Irano-Turanian region; Rangelands